The University of Virginia and the Creation of the American Campus - Wilson, Richard Guy (CIAN-Revista de Historia de las Universidades, 2014)
The history of collegiate architecture and planning in the United States is a complicated story that ranges from Thomas Jefferson’s University of Virginia which is widely hailed as one of the most cohesive and influential designs ever completed in North American to the opposite extreme of a miscellaneous collection of buildings lacking any overall order. From the initial beginning of American higher education in the 17th century to the present, colleges and universities have grown in size and complexity and have been analyzed in many books and studies. Jefferson’s original design of a large U shaped common ground planted with trees and bordered by rows of columns—larger in from the professor’s pavilions and smaller Tuscan order in front of the student dormitories, and capped by a large domed structure known as the Rotunda at one end still inspires. To understand the significance of Jefferson’s “Academical Village” at the University of Virginia and its impact one must consider the broader context and background of American institutions of higher learning and some of the issues and the special terminology employed.